Conservation Activities on Ancient Manuscript - Nur'aini, Nur'aini; Lubis, Habibah; Syam, Abdi Mubarak; Nasution, Laila Hadri; Siahaan, Hotlan; Azzahra, Dita; Rahmah, Mawaddah Savira (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
This research aims to determine ancient manuscript conservation activities. This research method uses a descriptive literature study approach. Data collection methods include reading, taking notes, and processing the contents of reading materials such as books, dictionaries, and journals. Researchers can gain a deeper understanding of the topic they are researching before conducting field research. By using valid and trustworthy sources, researchers can ensure that the research results they obtain have high validity and reliability. The results of this research show the importance of carrying out good conservation so that ancient manuscripts can be accessed and used by the public as a source of knowledge. Ancient manuscript conservation activities can be carried out by fumigation, removing acidity from the paper, repairing the manuscript (Lamination), as well as encapsulation and reproduction. These steps can be taken to prevent damage and protect ancient manuscripts that have cultural heritage value. Thus, conservation of ancient manuscripts not only aims to preserve cultural heritage, but also to ensure the continuity of research and scientific development in the future. Apart from that, conservation efforts carried out well will also provide long-term benefits for future generations, so that the knowledge contained in ancient texts can continue to be passed on and make a significant contribution to the development of society. Therefore, it is important for experts and related institutions to continue to support and carry out ancient manuscript conservation activities with full responsibility.